Penerapan Game Edukasi Terhadap Kemampuan Berpikir Kritis Dalam Pembelajaran Abad 21 - Farihatin Ni'mah; Wawan Shokib Rondli (ILUMINASI: Journal of Research in Education, 2023)
APPLICATION OF EDUCATIONAL GAMES TO CRITICAL THINKING ABILITY IN 21st CENTURY LEARNING. This study aims to analyze the increase in students' abilities through the application of educational games. This type of research is a classroom action research until two cycles. The research design uses the Kemmis and Taggart models which consist of planning, implementation, observation, and reflection. Data collection using observation,  test, field notes, and documentation. Data analysis techniques with quantitatively and qualitatively. The results of research on students' critical thinking skills experienced a significant increase. In cycle I, the average percentage of critical thinking skills is 73% in the good category, and in cycle II it becomes 91% in the very good category. Based on these results indicate that using educational games can improve critical thinking skills of elementary school students. This study suggests that teachers can use educational games that can motivate students to learn. The game is accompanied by HOTS questions to improve critical thinking skills.